The Influence of Work Stress and Workload on Auditor Performance with Work Motivation as an Intervening in the Inspectorate General of the Ministry of Agriculture of the Republic of Indonesia - Jatnika, Drajat; Yulianti, Tine (Dinasti International Journal of Management Science, 2024)
The success of national development requires the participation of skilled human resources. Civil Servants (PNS), for example, are part of the state apparatus which carries out the task of administering democratic, transparent government and development, providing quality and best possible services to the community. This research aims to determine the effect of work stress and workload on auditor performance with work motivation as an intervention at the Inspectorate General of the Indonesian Ministry of Agriculture. This research method uses a quantitative approach, a sample of 115 auditors who are still active at the Inspectorate General of the Ministry of Agriculture using the Slovin technique. The analysis method in this research uses the SEM-PLS method. The results of this research are that work stress and workload have a negative and significant effect on work motivation, work stress and workload have no effect and are not significant on auditor performance, work motivation has a positive and significant effect on auditor performance, work stress and workload have a negative effect and significant impact on Auditor Performance through work motivation as an intervening.